Maiko masquerade : crafting geisha girlhood in Japan - Bardsley, Jan (University of California Press, 2021)
"Maiko Masquerade explores Japanese representations of the maiko, or apprentice geisha, in films, manga, and other popular media as an icon of exemplary girlhood. Jan Bardsley traces how the maiko, long stigmatized as a victim of sexual exploitation, emerges in the 2000s as the chaste keeper of Kyoto's classical artistic traditions. Insider accounts by maiko and geisha, their leaders and fans, show pride in the training, challenges, and rewards maiko face. No longer viewed as a toy for men's amusement, she serves as catalyst for women's consumer fun. This change inspires stories of ordinary girls--and even one boy--striving to embody the maiko ideal, engaging in masquerades that highlight questions of personal choice, gender performance, and national identity"--